2021
DOI: 10.3390/s22010180
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Distance Measurement of Two Multisport Activity Trackers and a Cellphone App in Different Sports: A Cross-Sectional Validation and Comparison Field Study

Abstract: Options for monitoring sports have been continuously developed by using activity trackers to determine almost all vital and movement parameters. The aim of this study was to validate heart rate and distance measurements of two activity trackers (Polar Ignite; Garmin Forerunner 945) and a cellphone app (Polar Beat app using iPhone 7 as a hardware platform) in a cross-sectional field study. Thirty-six moderate endurance-trained adults (20 males/16 females) completed a test battery consisting of walking and runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
4
12
0
Order By: Relevance
“…The less accurate agreement r = 0.27 ( p = 0.057) of the SpO 2 minimum measurement of the Garmin device has no direct influence on the sleep stage calculation. Recent studies have shown mostly similar results with a high level of agreement between the measured vital data (HR, HRV and respiratory rate) against the PSG and ECG measurements [ 1 , 37 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 62%
“…The less accurate agreement r = 0.27 ( p = 0.057) of the SpO 2 minimum measurement of the Garmin device has no direct influence on the sleep stage calculation. Recent studies have shown mostly similar results with a high level of agreement between the measured vital data (HR, HRV and respiratory rate) against the PSG and ECG measurements [ 1 , 37 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 62%
“…The heart rate monitor used in this study is not a research-grade physiological monitoring device. While it has been validated as a heart rate measurement device during activities of moderate exercise intensity (Budig et al, 2021), the reported heart rate values might underestimate the heart rate of our participants (Jagim et al, 2020). Nonetheless, the comparison between baseline and exoskeleton heart rate is unlikely to be influenced by this discrepancy.…”
Section: Discussionmentioning
confidence: 85%
“…Another study conducted on thirty-six amateur endurance athletes tested the validity of the Polar Ignite and the Garmin Forerunner 945 watches for measuring distance [ 32 ]. That study revealed significant deviations for the Polar Ignite watch (min: −50 m; and max: 150 m) and for the Garmin Forerunner 945 watch (min: −30 m; and max: 90 m) for a 1.6 km interval run in an outdoor track and field [ 32 ].…”
Section: Discussionmentioning
confidence: 99%